Reflections on HLA Epitope-Based Matching for Transplantation - Duquesnoy, Rene J. (Frontiers in Immunology, 2016)
HLA antibodies are primary causes of transplant rejection; they recognize epitopes which can be structurally defined by eplets. There are many reviews about HLA epitope-based matching in transplantation. This article describes some personal reflections about epitopes including a historical perspective of HLA typing at the antigen and allele levels, the repertoires of antibody-verified HLA epitopes, the use of HLAMatchmaker in determining the specificities of antibodies tested in different assays and finally, possible strategies to control HLA antibody responses.